2014
DOI: 10.1021/ja5079877
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Approach to the Preparation of Chiral Sulfones by Ir-Catalyzed Asymmetric Hydrogenation

Abstract: Several chiral sulfonyl compounds were prepared using the iridium catalyzed asymmetric hydrogenation reaction. Vinylic, allylic and homoallylic sulfone substitutions were investigated, and high enantioselectivity is maintained regardless of the location of the olefin with respect to the sulfone. Impressive stereoselectivity was obtained for dialkyl substitutions, which typically are challenging substrates in the hydrogenation. As expected, the more bulky Z-substrates were hydrogenated slower than the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Certainly, a sulfone with an α‐proton has been widely used as a nucleophile in several C−C bond forming reactions, such as the Julia olefination and the Ramberg–Bäcklund reaction (Scheme a) . Vinyl sulfones, on the other hand, are among the most electron deficient/reactive alkenes and have been widely used as partners in ionic, radical additions and cycloadditions, or in the total synthesis of natural products (Scheme a) . Their importance is underlined by a recent literature review that stated that over 42 new syntheses of vinyl sulfones have been reported in the last five years alone .…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, a sulfone with an α‐proton has been widely used as a nucleophile in several C−C bond forming reactions, such as the Julia olefination and the Ramberg–Bäcklund reaction (Scheme a) . Vinyl sulfones, on the other hand, are among the most electron deficient/reactive alkenes and have been widely used as partners in ionic, radical additions and cycloadditions, or in the total synthesis of natural products (Scheme a) . Their importance is underlined by a recent literature review that stated that over 42 new syntheses of vinyl sulfones have been reported in the last five years alone .…”
Section: Methodsmentioning
confidence: 99%
“…However, the hydrogenation of the (Z)-configured sulfones turned out to be more problematic and lower conversions were generally observed, despite maintaining high stereoselectivity (Scheme 14). 21 Another example of enantiodivergence was reported in the Ir-catalyzed hydrogenation of allylic alcohols. Employing the same class of Ir-catalysts used for esters and sulfone derivatives, the Andersson group reported the hydrogenation of several aryl-and alkyl-substituted allylic alcohols in both (E)-and (Z)configuration.…”
Section: Cristiana Margaritamentioning
confidence: 99%
“…The preparation of hydroxy sulfones from β-ketosulfones in the presence of Ru [1920], Ir [21] and Rh [22] complexes was described. Chiral sulfones were also obtained by hydrogenation of the C=C bond with α,β-unsaturated sulfones in the presence of Ir(I) complexes with P,N-ligands [23].…”
Section: Introductionmentioning
confidence: 99%